2017
DOI: 10.3390/nu9111187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melatonin on Glucose Homeostasis, Antioxidant Ability, and Adipokine Secretion in ICR Mice with NA/STZ-Induced Hyperglycemia

Abstract: Diabetes is often associated with decreased melatonin level. The aim was to investigate the effects of different dosage of melatonin on glucose hemostasis, antioxidant ability and adipokines secretion in diabetic institute for cancer research (ICR) mice. Forty animals were randomly divided into five groups including control (C), diabetic (D), low-dosage (L), medium-dosage (M), and high-dosage (H) groups. Groups L, M, and H, respectively, received oral melatonin at 10, 20, and 50 mg/kg of BW (body weight) daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 45 publications
4
25
0
Order By: Relevance
“…There are some reports that hyperglycemia generally caused hypertriglyceridemia and hypercholesterolemia (48). The findings obtained from our study appear to be consistent with the data of researches conducted on the same subject (19,24,48). The positive changes observed in the plasma lipid parameters by the administration of melatonin are attributed to the reasons such as suppressed tissue lubrication (34,47), increased lipoprotein lipase activity and increased insulin sensitivity resulting in decreased a-c The difference between mean values with different superscripts in the same column is significant at the p<0.05 level 120 © 2019 Faculty of Sport Sciences, Selcuk University of lipolysis in adipose tissue (34).…”
Section: Discussionsupporting
confidence: 92%
“…There are some reports that hyperglycemia generally caused hypertriglyceridemia and hypercholesterolemia (48). The findings obtained from our study appear to be consistent with the data of researches conducted on the same subject (19,24,48). The positive changes observed in the plasma lipid parameters by the administration of melatonin are attributed to the reasons such as suppressed tissue lubrication (34,47), increased lipoprotein lipase activity and increased insulin sensitivity resulting in decreased a-c The difference between mean values with different superscripts in the same column is significant at the p<0.05 level 120 © 2019 Faculty of Sport Sciences, Selcuk University of lipolysis in adipose tissue (34).…”
Section: Discussionsupporting
confidence: 92%
“…Various experimental diabetes models have been proved to induce animal characteristic function and structural changes. These models include rats and mice that become diabetic after the administration of alloxan and STZ [7,8]. A limited study has been reported in the area of AA broiler diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…A limited study has been reported in the area of AA broiler diabetes. STZ is a DNA alkylating agent [8], and its intraperitoneal or intravenous injection caused marked infiltration of inflammatory cells and reduced insulin secretion leading to diabetes [9][10][11]. STZ may increase the production of ROS and inhibit enzyme activities related with the scavenging of free radical [12].…”
Section: Introductionmentioning
confidence: 99%
“…Since agomelatine is a melatonergic receptor agonist, its effects on glucose homeostasis are expected to be at least in part similar to melatonin effects. Melatonin has been reported not to reduce fasting blood glucose in STZ diabetic rat models [29][30][31][32]. Contrarily, several researchers suggested that melatonin lowered fasting blood glucose in STZ-or alloxaninduced diabetic rat models [33][34][35].…”
Section: Discussionmentioning
confidence: 99%